Fallow Weed Control with Preemergence Applications of Clarity, Atrazine, Spartan Guard, Sharpen, Zidua, and Corvus - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
Kochia control at 8 weeks after spring application (WAST) was greatest when Clarity (dicamba) was included in the spring applications or when Corvus (isoxaflutole + thiencarbazone) was applied with atrazine and Clarity in the fall. The best kochia control at 13 WAST occurred with spring applications containing Clarity. Only Clarity plus Atrazine, Sharpen, Zidua, Spartan Guard, or Corvus applied in the spring provided as much as 90% kochia control at 20 WAST. Only the spring application of Spartan Guard and Clarity controlled Russian thistle 90% at 20 WAST.
Keywords: fallow; weed control; preemergence applications; kochia; Russian thistle; spring-applied herbicides; Clarity; Dicamba; Atrazine; Spartan Guard; Sulfentrazone; Pendimethalin; Sharpen; Saflufenicil; Zidua; Pyroxasulfone; Corvus; Isoxaflutole; Thiencarbazone